Pop-up Retailing Managerial and Strategic Perspectives - Warnaby, Gary (SpringerBriefs in Business,, 2018)
This SpringerBrief offers an academic perspective on the trend of 'pop-up' retailing. It analyzes this temporary retail-oriented setting designed to foster a direct customer-brand interaction for a limited period, often with an explicitly promotional or communicative purpose. Adopting a managerial approach, it explores the use of pop-up retailing as a means of facilitating strategic growth by retail brands. In addition, it draws on theory from retail store environments and atmospherics, customer experience management and event management to provide an in-depth academic analysis of the planning and implementation issues arising from the inherent ephemerality of pop-up activities to achieve the strategic objectives of retail brands. The authors provide an overview of the entire pop-up lifecycle using an organizational schema that is split into four sequential stages: strategic objectives, pre-pop-up, actual pop-up experience, and the post pop-up stage. The key decision areas and activities incorporated in each of these stages are also outlined.